Sublime : 25 years of the Wesfarmers Collection of Australian Art - Wesfarmers Collection of Australian Art.; Carroll, Helen; Art Gallery of Western Australia; Wesfarmers ([Perth] : Wesfarmers Arts, 2002)
A catalogue of the Sublime exhibition, presented by the Art Gallery of Western Australia.
Authors: Helen Carroll, Betty Churcher, Brenda L. Croft, Rachael Kohn, David Malouf, Margaret Seares.
"Art Gallery of Western Australia, 2 October - 24 November 2002".
"A Wesfarmers Limited exhibition in association with the Art Gallery of Western Australia".
Keywords: Wesfarmers -- Art collections -- Exhibitions; Wesfarmers Collection of Australian Art -- Exhibitions; Painting, Australian -- Exhibitions; Art -- Private collections -- Western Australia -- Perth -- Exhibitions; Art, Australian -- Exhibitions; Art - Art motifs - Dot; Art - Painting; Art - Economic aspects - Markets - Market places; Art - Art motifs; Art - Art motifs - Abstract; Western Australia (WA)